Making better pricing decisions with informative priors - Montgomery, Alan L. (Henry Stewart Talks, 2010)
Bayesian theory and informative priors, Using statistical models for making pricing decisions, Sales response models, Exchangeable priors: hierarchical Bayesian models, Implication: shrinkage estimators, Store-level strategies, Theory based priors, Informative priors, Additive utility structure, A simulated example, Elasticity estimates, Eliciting priors using experts, Constraints as business rules, Empirical application, Rejecting sampling, Final recommendations